1998
DOI: 10.1037/0021-843x.107.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset for binge eating and purging during late adolescence: A 4-year survival analysis.

Abstract: This prospective study examined age of onset for binge eating and purging among girls during late adolescence and tested whether dieting and negative affectivity predicted these outcomes. Of initially asymptomatic adolescents, 5% reported onset of objective binge eating, 4% reported onset of subjective binge eating, and 4% reported onset of purging. Peak risk for onset of binge eating occurred at age 16, whereas peak risk for onset of purging occurred at age 18. Adolescents more often reported onset of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
200
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 229 publications
(222 citation statements)
references
References 18 publications
18
200
3
1
Order By: Relevance
“…This is not surprising, given that eating disorder symptoms typically emerge in late adolescence (ages 16-18; Stice et al 1998) while our sample was comprised of young adolescents (aged 11-13). Hispanic females and Black males reported higher levels of eating pathology than individuals from other racial/ethnic groups; however, only racial/ethnic differences in food preoccupation among males reached statistical significance.…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising, given that eating disorder symptoms typically emerge in late adolescence (ages 16-18; Stice et al 1998) while our sample was comprised of young adolescents (aged 11-13). Hispanic females and Black males reported higher levels of eating pathology than individuals from other racial/ethnic groups; however, only racial/ethnic differences in food preoccupation among males reached statistical significance.…”
Section: Discussionmentioning
confidence: 90%
“…Third, because we focused solely on adolescents, our results should also be generalized with caution to younger or older populations. Again, however, we focused on adolescence because this is the peak risk period for onset of bulimic pathology (Stice et al, 1998). Fourth, we used body mass as our indicator of adiposity.…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
“…At any point in time, 40-45% of girls and young women are trying to lose weight through various means motivated by "normative" body dissatisfaction (French, Story, & Neumark-Sztainer, 1997;Striegel-Moore, Silberstein, & Rodin, 1986). Killen, Hayward, & Taylor, 1998), and prevalence rates are much higher among female college students than in the general population or among men (Dancyger & Garfinkel, 1995).…”
mentioning
confidence: 99%
“…These programs (a) are offered to high-risk individuals because they may be more willing to commit to the intervention due to their high levels of distress and because they are most likely to evidence change as a result of the treatment (Stice, Mazotti, Wiebel, & Agras, 2000;Stoolmiller, Eddy, & Reid, 2000), and (b) utilize interactive exercises and homework to apply and integrate the skills taught in the intervention (Stice & Shaw, 2004). Further, college students are an ideal group to target for such interventions because eating pathology is most likely to emerge during this time of life (Lewinsohn, 2000;Stice, Killen, Hayward, & Taylor, 1998), and because programs are most effective when delivered during the period in which eating disorder symptoms are emerging (Maggs, Schulenberg, & Hurrelmann, 1996).In a meta-analysis of eating disorder prevention and intervention programs, Stice and Shaw (2004) found that 53% of the interventions resulted in significant reductions in 4 at least one established risk factor for eating pathology, such as body dissatisfaction. In addition, most of the programs that reduced eating pathology did so by focusing the intervention on the previously established psychosocial risk factors, such as internalization and negative affect.…”
mentioning
confidence: 99%
See 1 more Smart Citation